Positive and nodal solutions for parametric superlinear weighted (p, q)-equations. (June 2023) - Papageorgiou, Nikolaos S.; Scapellato, Andrea
Abstract: We consider a nonlinear eigenvalue problem for equations driven by a weighted ( p, q ) -Laplacian and a superlinear reaction. We prove a global (with respect to the parameter λ > 0 ) existence and multiplicity result. We also generate nodal (sign-changing) solutions. Finally, we determine the topological properties of the solution set and prove the continuity properties of the solution multifunction.